Perancangan Media Interaktif Mobile Augmented Reality (AR) Dalam Pendidikan Untuk Pembelajaran Kesehatan - Yoga Yoga Sahria; Nur Azizah; Gugum Saefuloh Zidni; Nurul Isnaini Febriarini (Universitas Negeri Padang, 2022)
Abstract− Augmented Reality (AR) is a technology that is developing rapidly nowadays, the use of Augmented reality technology is widely used in various fields, one of which is health. The application of augmented reality to health is not only done technically but also in the form of learning. There are still many things that have not been achieved regarding Health education. This research was conducted to realize innovative and interesting learning for students, this application is designed to simplify, save costs and increase student interest in learning without having to reduce the information conveyed. The result of this research is the Design of an Augmented Reality Mobile Application for health that focuses on learning. Test results 80% of students said that 80% said they were very good at implementing AR applications for health learning.